2022
DOI: 10.3390/en15041548
|View full text |Cite
|
Sign up to set email alerts
|

Flow Deflection between Guide Vanes in a Pump Turbine Operating in Pump Mode with a Slight Opening

Abstract: During the startup and shutdown processes of a reversible-pump turbine (RPT) working in pump mode, abnormal sounds and vibrations usually occur in the distributor when the guide vanes (GVs) are at a slight opening (max opening of about 6%). The objective of this paper is to apply a three-dimensional numerical CFD method to study the unsteady flow behavior in the guide vane region of a pump turbine operating in pump mode. The dynamic meshing technique is introduced to simulate the startup and shutdown processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This paper uses the continuity equation based on incompressible fluid and the time-averaged Reynolds equation (RANS equation), and the RNG k-ε model was used for the turbulence model. Several studies [23,24] have revealed that the RNG k-ε model can predict the swirling flow and vortex flow very well, and has good applicability in the flow field of the axial flow pump.…”
Section: Governing Equationmentioning
confidence: 99%
“…This paper uses the continuity equation based on incompressible fluid and the time-averaged Reynolds equation (RANS equation), and the RNG k-ε model was used for the turbulence model. Several studies [23,24] have revealed that the RNG k-ε model can predict the swirling flow and vortex flow very well, and has good applicability in the flow field of the axial flow pump.…”
Section: Governing Equationmentioning
confidence: 99%
“…They found that the length of the lap between guide blades is closely related to the self-excited oscillation of guide vanes, and the vibration problem can be improved by modifying the profile [4]. The dynamic meshing technique was adopted to simulate the starting up and shutting down processes by Q F Ji and H G Fan, to capture the flow details between the guide vanes [7,8,9]. They found that there is bistable flow between guide vanes in pump condition, which was believed to be the cause of abnormal vibration.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing the torque variation rate of a single guide vane and CFD flow simulation, they found that the repeating reversal of fluid in the guide vane region is the cause of vibration during load rejection. Ji et al [7] investigated abnormal sounds and vibrations occurring in the distributor of a reversible pump-turbine when guide vanes were slightly opened (maximum opening of about 6%) during the pump mode. They applied a three-dimensional numerical CFD method to study the unsteady flow behaviour in the guide vane region of a pump-turbine operating in pump mode.…”
Section: Introductionmentioning
confidence: 99%